Spiritualitas Islam dalam Trilogi Kosmos - Munawir Haris (Universitas Islam Negeri Mataram, 2013)
Human beings are mysterious. Although various studies about humans have been conducted, they fail to totally comprehend them. Therefore, studies about humans are always interesting topics, especially if they attempt to reveal non-physical aspects of humans. One way to look at this neglected aspect is to study spiritual dimensions of humans. Base on their explorations to the Qur’an and hadith, Muslim scholars propose a theory of three cosmos: macrocosmos, microcosmos and metacosmos. Macrocosmos represents the Universe. Microcosmos is human beings and metacosmos is concerned with Allah. These are three cosmologies that Muslims have to find from the scriptural texts so they can understand the central role of human beings in preserving balanced relationships among these three worlds. The Qur’an, for example, gives allegories and signs that Muslims must explore their deep meanings to gain wisdom and get closer to the Creator.